Smokers Display Reduced Glucocorticoid Sensitivity Prior to Symptomatic Chronic Disease Development. Issue 10 (25th January 2018) - Bennett, J M; Marino, J S; Peck, B; Roos, L G; Joseph, K M; Carter, L B; Smith, C B; Rohleder, N; Coffman, M J
Abstract: Background: Chronic stress plays a critical role in many of today's diseases and causes of death. Tobacco use reliably increases the likelihood of chronic disease development and premature death. In addition, habitual tobacco use elevates risk of chronic inflammatory diseases, and glucocorticoid therapy is often less effective in smokers compared with nonsmokers. Taken together, smokers may develop glucocorticoid insensitivity, thereby removing the body's greatest anti-inflammatory mechanism. Purpose: The purpose of this study was to examine glucocorticoid sensitivity among 24 smokers and 24 age-, sex-, and body mass index-matched never smokers who were clinically healthy individuals (i.e., no diagnosis or medication use for chronic diseases and normotensive). Method: Participants visited the lab after a 12 hr fast, provided a blood sample, and completed a series of psychosocial questionnaires. Smokers continued smoking ad libitum before the lab visit. Group differences in glucocorticoid sensitivity were examined using ANCOVA and repeated with linear mixed model to account for possible dependence among immune outcomes that matching participants on age, sex, and body mass index may have introduced. Results: Prior to clinical disease onset, smokers' peripheral blood mononuclear cells (PBMCs) exhibited reduced glucocorticoid sensitivity as well as a diminished inflammatory response to lipopolysaccharide compared with never smokers' PBMCs; results were identical regardless of statistical modeling used. Conclusions: Cigarette smoking, a self-initiated pharmacological chronic stressor, may provide a unique opportunity to examine early wear and tear on physiological functioning that may lead to chronic disease development. Additional research into PBMCs' intracellular changes must be examined as well as repeating this study in a larger, more heterogeneous population. Abstract : Prior to chronic disease diagnosis, immune cells from smokers were less responsive to cortisol's anti-inflammatory effects compared to those from never smokers.